The Effect of Leadership and Reward System on Patient Safety Culture Mediated by Nurses' Motivation in Satya Negara Sunter Hospital - Dharmawan, Hery; Ruswanti, Endang; Kusumapradja, Rokiah (Jurnal Health Sains, 2025)
This study examines the impact of leadership and reward systems on patient safety culture at Satya Negara Sunter Hospital, with nurse motivation serving as a mediating factor. The need for effective patient safety practices in healthcare environments underscores the importance of leadership, rewards, and motivation. This quantitative study used a cross-sectional design and surveyed 120 nurses through a structured questionnaire. Data analysis was performed using Partial Least Squares (PLS) to assess the direct and indirect effects of the variables. The results indicate that both leadership and reward systems significantly influence patient safety culture, with nurse motivation mediating these relationships. The findings emphasize that leadership enhances nurse motivation, while a transparent reward system further boosts motivation and strengthens the patient safety culture. This study contributes to organizational behavior theory by highlighting the interconnections between leadership, reward systems, and motivation in fostering a culture of safety. Practical recommendations include strengthening leadership capabilities, optimizing reward programs, and improving nurse motivation to ensure high-quality healthcare services.